A Study of English Adjective Based Weather Collocations and Their Vietnamese Equivalents - Lê Thị Thu Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study aims at investigating English collocations formed along with the adjectives related to weather with reference to their Vietnamese equivalents in terms of semantic modelling based on the Frame suggested by Fillmore (1982). Hence, the study’s findings cancontribute to the better understanding of the English adjective-based collocations denoting weather, which facilitates the comprehensionand application in composing speeches for English learners, teachers